Optimization of 3D Printing Parameters of High Viscosity PEEK/30GF Composites - Stepanov Dmitry Yurjevich D. Yu.; Dontsov (Doncov) Yu. Yuriy Vladimirovich; Panin S. V. Sergey Viktorovich; Buslovich D. G. Dmitry Gennadjevich; Aleksenko V. O. Vladislav Olegovich; Bochkareva Svetlana Alekseevna S. A.; Batranin A. V. Andrey Viktorovich; Kosmachev Pavel Vladimirovich P. V. (2024, 2024)
Title screen